OPTIMIZING POST-STROKE REHABILITATION: COMPARING THE EFFECTIVENESS OF PHARMACOPUNCTURE, KINESIOTHERAPY, KINESIOTAPING, REFLEXOTHERAPY, AND KORVIT DEVICE - Kim O.A., Bebitova Sh.E., Saydaliyeva S.Sh., (Central Asian Journal of Medicine, 2025)
Motor dysfunction after stroke remains one of the main challenges in the patient’s recovery process. Timely and well-structured rehabilitation can significantly improve movement, reduce complications, and restore independence. This study compares two modern rehabilitation approaches used in the early recovery phase of ischemic stroke. The first group of patients received a combination of pharmacopuncture, kinesiotherapy, and kinesiotaping. The second group was treated with reflexotherapy using the "Korvit" device. A third group received only standard rehabilitation methods. Clinical results were assessed using the Fugl-Meyer Scale, Barthel Index, and Modified Ashworth Scale. After a six-week course, the first group showed the most significant improvements in motor activity and reduction of spasticity. The second group also demonstrated better outcomes than the control group. These findings suggest that the use of combined and integrative rehabilitation techniques may increase the effectiveness of stroke recovery programs and help optimize treatment strategies in clinical practice.